IMPLEMENTASI BEBERAPA UJI KENORMALAN OMNIBUS DENGAN PERANGKAT LUNAK R - I WAYAN SUMARJAYA (Jurnal Matematika, 2010)
An omnibus normality test is a normality test that can give additional information about nonnormalityor other deviation from normality through the skewness and the kurtosis coefficients. The aim of thisresearch is to implement the omnibus D’Agostino-Pearson K2 test and modified Jarque-Bera teststatistic using R software.